Critical success criteria for B2B E-commerce systems in Chinese medical supply chain. Issue 2 (3rd March 2016) - Wang, Chengbo; Mao, Zhaofang; Johansen, John; Luxhøj, James T.; O'Kane, James; Wang, Jun; Wang, Liguo; Chen, Xuezhong
Abstract : The paper presents an exploratory investigation to determine and prioritise the critical success criteria, which can measure and guide the successful application and performance improvement of business to business e-commerce system (BBECS) in a medical supply chain's selling and buying functions, in the context of global business expansion. The research reveals that the buying and the selling functions have different prioritisations on the majority of the determined critical success measuring criteria. These criteria are categorised into three Critical Success Measuring Criteria Groups, for the selling and the buying functions, respectively, guiding medical supply chain members in harnessing the full advantage of a BBECS. For the selling function, the top critical success measuring criteria are as follows: integrating information searching/transmission and application processes, ensuring the reliability and timeliness of technical support, ensuring recognition and acceptance of e-commerce processes, displaying the organisation's business focus and product/service provisions online, securing a large scale/amount of business transactions, adjusting production outputs and inventory levels and having more registered users than competitors do. The top critical success measuring criteria for the buying function are as follows: securing the establishment of business relationships between businesses, displaying the measures ensuring mutual trust and cooperation online, ensuring employees' recognition of the benefit of e-commerce in increasing revenue, ensuring the contribution to the development and realisation of corporate strategy, achieving cost reduction for the organisation, making the purchase of famous brand products available/doable, securing a large scale/amount of business transactions, and ensuring the attainability of products/services at a lower price.